Teacher self-efficacy as an aspect of narrative self-schemata. (January 2022) - Marschall, Gosia; Watson, Steven
Abstract: This study represents a theoretical investigation of teacher self-efficacy using abductive interpretative phenomenological analysis in the context of initial teacher education. We reveal the process through which a pre-service teacher's self-schema adapts in response to his first classroom teaching experience. We also observe that narrative has a role in this self-schema adaptation. Consequently, we show that teacher self-efficacy is an aspect of a more generalised narrative self-schema. This offers an alternative perspective on how teacher self-efficacy is developed. It contributes to a deeper understanding of pre-service teachers' professional learning and a new understanding of the concept of self-efficacy more generally. Highlights: Narrative imagination is central to how we make sense of affective experiences and cope with complex demands of our lives. Teacher self-efficacy appraisal attends to wider conceptualisations of narrative self or narrative self-schema. Teacher self-efficacy is in much closer relationship with narrative identity formation than previously articulated.